Identification of aspergillus species isolated from Corn and peanuts in storage godowns - R.THILAGAM; N. HEMALATHA; E.POONGOTHAI; G.KALAIVANI (International Journal of Pharma and Bio Sciences, 2016)
The aim of this study was to identify aflatoxin producing fungi from affected corn and peanut samples collected from the storage godowns. Fungi were isolated from corn and peanuts using potato dextrose agar and modified rose bengal agar. The pure culture of the isolates were grown on differential media namely malt extract agar, czapek yeast extract agar and czapek dox agar for species identification using macro morphological characteristics. Lacto phenol cotton blue stains were used to identify fungal microscopic structures. All the fungi belonged to Aspergillus species. The fungal isolates were tested for aflatoxin producing ability. Out of the five different Aspergillus species isolated, two species namely A.flavus and A.parasiticus producedaflatoxin in the Aspergillus flavus parasiticus agar medium (AFPA) and Aspergillus differentiation medium (ADM).Early detection may help to bring in early management and control practices.